Classic drugs in the time of new drugs: real‐world, long‐term outcomes of thiopurine monotherapy in 1016 patients with inflammatory bowel disease. Issue 6 (6th July 2022) - Rezazadeh Ardabili, Ashkan; Jeuring, Steven; Mujagic, Zlatan; Oostenbrug, Liekele; Romberg‐Camps, Mariëlle; Jonkers, Daisy; van Bodegraven, Adriaan; Pierik, Marieke
Summary: Background: Thiopurines remain recommended as maintenance therapy in patients with inflammatory bowel disease (IBD). Despite their widespread use, long‐term effectiveness data are sparse and safety is an increasingly debated topic which thwarts proper delineation in the current IBD treatment algorithm. Aims: To document effectiveness and safety of thiopurine monotherapy in patients with IBD, using the population‐based IBD South‐Limburg (IBDSL) cohort Methods: All patients starting thiopurine monotherapy as maintenance between 1991 and 2014 were included. Therapy was defined as effective if there was no escalation to biologicals, no course of corticosteroids, no surgery and no hospitalisation for active disease during treatment. Long‐term effectiveness was assessed by adjusting for differences in follow‐up using Kaplan–Meier analyses. Mid‐ to long‐term safety regarding cancer incidence and clinically relevant liver disease was documented. Results: In total, 1016 patients (643 Crohn's disease [CD]; 373 ulcerative colitis [UC]) received thiopurine monotherapy at a median of 15.2 (Q1‐Q3 4.2–48.5) months after diagnosis. During follow‐up, effectiveness rates at 1, 5 and 10 years were 64%, 45%, 32%, respectively, in CD and and 66%, 41%, 36%, respectively in UC. No statistically significant differences in effectiveness were observed after stratification for era of initiation (pre‐biological vs biological, CD: p  = 0.56; UC: p  = 0.43). Sixteen non‐melanoma skin cancers (incidence rate [IR] 3.33/1000 PY), five lymphomas (IR 1.04/1000 PY) and one urinary tract cancer (IR 0.21/1000 PY) were recorded. Two cases of portal hypertension were identified. Conclusion: In real‐world practice, thiopurine monotherapy remains effective, safe and durable for patients with CD or UC, including in the era of biologics. Abstract :